2021
DOI: 10.1063/5.0048609
|View full text |Cite
|
Sign up to set email alerts
|

Effects of divertor electrical drifts on particle distribution and detachment near the divertor target plate in DIII-D

Abstract: Strong impacts of drifts on the divertor plasma in-out asymmetry and detachment are demonstrated in DIII-D with an open divertor configuration. For forward toroidal field, B T , i.e., with the ion B Â rB drift toward the divertor, the particle flux to the inner divertor, as represented by the Langmuir probe measured ion saturation current (J sat ), exhibits a double peak structure, with electron temperature, lower at the inner target. Reversing the B T direction reverses both the radial and poloidal E Â B flow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 44 publications
4
16
0
Order By: Relevance
“…In this paper, we carry out an analysis on the formation of the double-peak density profile with a focus on an unfavorable B t configuration. The simulation qualitatively reproduces the dependences of the doublepeak profile on heating power and density observed in experiments [5,11]. The results demonstrate that the formation of a doubly peaked density profile requires two conditions: (1) buildup of a broad high-density region by radial particle transfers via E p × B drift; (2) creation of a strong enough particle sink by reversed particle flux (pointing away from the target) originated from E r × B drift.…”
Section: Introductionsupporting
confidence: 61%
See 1 more Smart Citation
“…In this paper, we carry out an analysis on the formation of the double-peak density profile with a focus on an unfavorable B t configuration. The simulation qualitatively reproduces the dependences of the doublepeak profile on heating power and density observed in experiments [5,11]. The results demonstrate that the formation of a doubly peaked density profile requires two conditions: (1) buildup of a broad high-density region by radial particle transfers via E p × B drift; (2) creation of a strong enough particle sink by reversed particle flux (pointing away from the target) originated from E r × B drift.…”
Section: Introductionsupporting
confidence: 61%
“…Detached or partially detached divertor operations with acceptable levels of heat flux density and plasma temperature are required to facilitate steady-state scenarios within foreseen technologies for plasma-facing components. Plasma distributions and the associated convective and conductive transport in the divertor and scrape-off layer (SOL) are crucial in affecting the way of approaching divertor detachment [4][5][6][7].the Doubly peaked density and particle flux profiles have repeatedly been observed in many tokamaks, including but not limited to JET [8,9], DIII-D [5,10], and EAST [11]. The double-peak distribution can influence the plasma-wetted area where heat flux is deposited, and affect the way of divertor detachment.…”
Section: Introductionmentioning
confidence: 99%
“…These drifts have directional characteristics and typically have magnitude on the order of 1 km s −1 in the poloidal direction and 0.1 km s −1 in the radial direction. [ 47,48 ] As shown in this study, the perpendicular ion transport due to the elastic scattering broadens the plasma density profile. This transport may contribute to the ion movement from higher density regions to lower density regions.…”
Section: Numerical Resultsmentioning
confidence: 64%
“…It is unfortunate that in the experiment reported in this paper, there were no density, temperature and radial electric field measurements near the divertor region. It is suggested that the E × B drift in the SOL near the divertor may affect the upstream flow properties and impact the transition process [21,22]. This will be studied in future experiments with more data obtained in the SOL divertor region.…”
Section: Summary and Discussionmentioning
confidence: 99%